An Analysis of Students' Ability in Reading Descriptive Text at Grade 8 of SMPS Panca Jaya Galang - Lidya Lorenza Septina Zalukhu; Royani Situmorang; Suci Silviana Aswa; Natali Widya Pasca Tarigan; Nurteteng Nurteteng (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to analyze of students’ ability in reading descriptive text. Respondents in this study consisted of 20 students grade 8. This research was conducted at SMPS Panca Jaya Galang, Jl. Sei Karang Kampung Agam Galang. The method used in this research is qualitative method. Data was taken through test and questionnaires. The result showed that the average score of the students’ ability to reading descriptive text is 40. The test result showed that there were 2 students who got a score of 10, there were 2 students who got a score of 30, there were 10 students who got a score of 40, there were 4 students who got a score of 50, there are 2 students who get a value of 60. Therefore, it can be concluded that the of students’ ability in reading descriptive text is “low”.